Photo-mediated synthesis of halogenated spiro[4, 5]trienones of N-aryl alkynamides with PhI(OCOCF3)2 and KBr/KCl. Issue 10 (26th February 2020) - Liu, Tong; Li, Yaming; Jiang, Linlin; Wang, Jiaao; Jin, Kun; Zhang, Rong; Duan, Chunying
Abstract : A novel and convenient photo-mediated halogenated spirocyclization of N -( p -methoxyaryl)propiolamides has been developed. Abstract : A novel and convenient photo-mediated halogenated spirocyclization of N -( p -methoxyaryl)propiolamides has been developed. The photolysis of phenyliodine bis(trifluoroacetate) (PIFA) as an iodination reagent led to iodinated ipso -cyclization under the irradiation of a xenon lamp, while brominated ipso -cyclization or chlorinated ipso -cyclization was achieved by irradiating a mixture of PIFA and KBr/KCl under a blue LED. The present protocol simply utilizes light as the safe and clean energy source and doesn't require any external photocatalyst providing various 3-halospiro[4, 5]trienones in good to excellent yields (up to 93%).